(untitled) - Burton, L. DeVere; L. DeVere Burton (Clifton Park, NY, 2007)
Introduction to Forestry Science, Second Edition, is an introductory forestry book that covers the principles and practices of forest management that integrates an applied science approach. Processing of wood and forest products, the economic impact of forests on the U.S. economy, and government historical events and policies that have influenced forest management practices are included. Current laws and regulations that govern the uses of forests are also addressed. Science topics covered include cell structure and function, cell growth and reproduction, elemental cycles, principles of ecology, the food pyramid, plant anatomy and physiology, entomology, water quality, air quality and preservation of endangered species. In addition, career options related to forests and forest management and the skills necessary to obtain employment are addressed.
Keywords: Forests and forestry; Forest management; Forests and forestry; Forest management